Penerapan Media Pembelajaran Berbasis Video Dalam Meningkatkan Motivasi Belajar Siswa Kelas 1 SD Bali Bilingual School - Purnami, Ni Made Ayu; Utami, Putu Budi (Jurnal Media Informatika, 2024)
Learning media is a medium used in the learning process to convey messages or materials when learning begins so that it can run well. Learning videos are media specifically designed to be used as learning resources for students. Examples include videos that present learning materials with the help of audio-visual aids to increase appeal, simulation videos of tool use, videos that record events relevant to the learning material, video songs containing learning information, and films that present learning materials. This study used a qualitative descriptive research method by conducting observations, interviews, classroom action research aimed at increasing the learning motivation of grade 1 students of Bali Bilingual School Elementary School. The results of the study showed that students were very happy when learning using video media and also the increase in student learning before and after watching learning videos increased greatly. The results of this study indicate that the application of video-based learning media in grade 1 of Bali Bilingual School Elementary School significantly increases student learning motivation. Students show high enthusiasm for learning using videos, children will feel more interested and actively participate in learning activities.